Three weeks with my brother [compact disc, unabridged] - Sparks, Nicholas (Time Warner Audiobooks, 2004)
In January 2003, Nicholas Sparks and his brother Micah set off on a three week trip around the world. It was to mark a milestone in their lives, for at 37 and 38 respectively, they were now the only surviving members of their family. Against the backdrop of their trip, the Sparks brothers learn about loss, love, and hope.